Broomrape (Orobanche sp.) Management in Indian Mustard - Das, Tanmay; Singh, Teekam; Sonnad, Prakash (Chronicle of Bioresource Management, 2023)
Broomrape (Orobanche sp.) is a root holoparasitic plant resulting in significant yield losses (5-100%) in the crops of leguminous, oilseeds, solanacious, cruciferous and medicinal plants in the drier and hotter regions. In India, Orobanche is a “super sink” to mustard and become threat to mustard production. The long-term effects of broomrapes are considerably worse because its seeds are quickly dispersed to adjacent fields and remained viable in the soil for up to 20 years. Broomrape can be controlled through physical techniques viz., weeding, soil tillage, flooding, irrigation, solarization and burning; chemical method viz., soil fumigation, herbicide application, and germination stimulants, and biological techniques like use of resistant or tolerant varieties, cropping systems with trap and catch crops, intercropping, biological control with insects or fungi. However, integrated management strategies are very useful as single technique is not effective and inexpensive.